Analisis Kinerja Keuangan Perusahaan Dengan Rentabilitas Ekonomi Dan Economic Value Added (EVA) Pada Perusahaan Jasa Transportasi Dan Logistik Yang Terdaftar Di Bursa Efek Indonesia - Verananda, Vidiatama Octa; Arisyahidin, Arisyahidin (Otonomi, 2024)
The high level of public need for transportation has encouraged entrepreneurs to develop transportation technology. They compete to attract public interest so that they are interested in using their services in order to increase company profits. In this research the author will analyze the influence of financial performance using the economic profitability method with indicators of Return on Assets (ROA), Return on Equity (ROE) and Economic Value Added (EVA) in 10 transportation and logistics service companies listed on the Indonesia Stock Exchange. The data taken is financial report data for transportation and logistics service companies listed on the Indonesia Stock Exchange in 2018-2022 in the form of balance sheets, profit and loss reports, or the company's annual financial reports. After analyzing the economic profitability method with the Return on Assets (ROA) indicators, Return on Equity (ROE) indicators, it can be concluded that the financial performance results using the ROA and ROE methods of the 10 companies tend to fluctuate every year. Meanwhile, the financial performance results using the EVA method from 10 companies also tend to fluctuate every year.